3(2n-4)=(8n+6)+9

Simple and best practice solution for 3(2n-4)=(8n+6)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2n-4)=(8n+6)+9 equation:


Simplifying
3(2n + -4) = (8n + 6) + 9

Reorder the terms:
3(-4 + 2n) = (8n + 6) + 9
(-4 * 3 + 2n * 3) = (8n + 6) + 9
(-12 + 6n) = (8n + 6) + 9

Reorder the terms:
-12 + 6n = (6 + 8n) + 9

Remove parenthesis around (6 + 8n)
-12 + 6n = 6 + 8n + 9

Reorder the terms:
-12 + 6n = 6 + 9 + 8n

Combine like terms: 6 + 9 = 15
-12 + 6n = 15 + 8n

Solving
-12 + 6n = 15 + 8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-8n' to each side of the equation.
-12 + 6n + -8n = 15 + 8n + -8n

Combine like terms: 6n + -8n = -2n
-12 + -2n = 15 + 8n + -8n

Combine like terms: 8n + -8n = 0
-12 + -2n = 15 + 0
-12 + -2n = 15

Add '12' to each side of the equation.
-12 + 12 + -2n = 15 + 12

Combine like terms: -12 + 12 = 0
0 + -2n = 15 + 12
-2n = 15 + 12

Combine like terms: 15 + 12 = 27
-2n = 27

Divide each side by '-2'.
n = -13.5

Simplifying
n = -13.5

See similar equations:

| 35+11x=2x-100 | | -84=-8+2(8p-6) | | x^2=4x+12 | | x+19+4x=-41-4x-48 | | 59=-51+10x | | 36x^2-54x-360=0 | | -12x-20=-10x+100 | | 8y+3(y-5)=4(y+1)-2 | | 18.10x=63.35 | | 17-6x=9+2x | | x^3+5x^2+7x-8=0 | | 3x-3(5x+4)=-72 | | 1.6=18.10x | | 8-7(-8r-2)=-426 | | 5x-5=6x+8 | | -9y= | | 7v*2-9v= | | -6z-z=7z-7-9z | | 10x-4=x-4 | | -x+8=21 | | -15x=10 | | 5b-8(1+8b)=-126 | | 18.10x=1.1 | | 11x+72=-126 | | 4(4x+4)=6(x-2) | | -x=-20 | | 28x^3+88x^2-37x-7=0 | | 58+6x=x-47 | | 1.8x-5.4=-5 | | 6(3+2x)-2=76 | | -41=37+6x | | -7-(-9)= |

Equations solver categories